Outcome of Low Molecular Weight Heparin Use in Pregnant Women with Oligohydramnios at A Tertiary Care Hospital: Heparin Use in Pregnant Women with Oligohydramnios - Tabassum, Shagufta; Tarin, Ayesha Uzaima; Suman, Faiza; Nawaz, Nyla; Rao, Saima Ayaz; Mukhtar, Hina (Pakistan Journal of Health Sciences, 2025)
Oligohydramnios refers to an antenatal condition in which the amniotic fluid volume is abnormally low and has poor fetal consequences. This research strives to elaborate on the convoluted connections between oligohydramnios and the associated maternal and fetal risks. Objectives: To find out the frequency of pregnancy outcomes in pregnant women with oligohydramnios using low molecular weight heparin (LMWH). Methods: The prospective cohort study was conducted at the Obstetrics Department of Nishtar Hospital, Pakistan from November 2024 to January 2025. One hundred and twenty-two women fulfilling the inclusion criteria were included. Patients were given 40 mg LMWH subcutaneously once a day. The patients were followed till delivery to determine outcomes including live birth, preterm delivery, weight at birth, admission to the Neonatal Intensive Care Unit (NICU) and pre-eclampsia. SPSS version 26.0 was employed to analyze the data. Results: Out of 122 participants, 120 (98.4%) resulted in live births while 2 (1.6%) were intra-uterine deaths. Among all births, 21 (17.2%) were delivered preterm while 101 (82.8%) were delivered at term. 108 (88.5) weighed >2.5 kg. Among 120 live births, 23 (19.2%) were admitted to the NICU for observation or treatment. Conclusions: It was concluded that the study results support the use of LMWH in oligohydramnios as a proportion of adverse perinatal outcomes was low in our study. LMWH was found to be efficacious, authentic and safe in oligohydramnios to achieve desired clinical outcomes and decrease the burden of associated morbidities and mortalities in the targeted population.